Immune response to multi-epitope Blomia tropicalis hybrid protein in mice - Dalgys Martínez; Brenda Flam; Helber Herazo; Inés Benedetti; Narasaiah Kolliputi; Luis Caraballo; Richard F. Lockey; Leonardo Puerta (Revista Alergia México, 2018)
Background: The mite Blomia tropicalis (Blo t) is an important source of allergens and a major risk factor for allergic rhinitis and asthma. A hybrid protein that includes epitopes of allergens Blo t 1, Blo t 5, Blo t 10, Blo t 12 and Blo t 13 (BTx5) and shows low IgE reactivity in sera from house dust mite allergic subjects was reported previously. This study evaluated the BTx5 immune response in BALB/c mice.